Penguatan Usaha Mikro Kecil dan Menengah (UMKM) Melalui Berbagai Model Skema Pendanaan di Indonesia: Sebuah Telaah Konseptual - Eko Suyono (JBIMA (Jurnal Bisnis dan Manajemen), 2017)
Small and medium enterprises (SMEs) are the main pillars of a country economy, especially in developing countries. Actually, the existence of this type of business in Indonesia has been since the Dutch colonial era long decades ago. However, nowadays its existence is threatened due to the rapid expansion of modern businesses that spread into rural areas of Indonesia. Therefore, under full of limitations, SMEs are in dire need of government assistance, both central and local governments in term of financial and nonfinancial to strengthen the SMEs' capital so they are able to sustain their businesses. This paper intends to analyze several financing scheme model for SMEs that could be given by the government through financial institutions so that the SMEs will be getting an easy access to the capital resources. In the other word, this condition is expected to give maximum support for SMEs development. As a result, the SMEs will contribute to eradicating unemployment and poverty by strengthening county economy.